PENGARUH INSENTIF MATERIAL DAN INSENTIF NON MATERIAL TERHADAP EFEKTIVITAS KERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PAREPARE - Amalia, Magfirah (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to describe and analyze the Effect of Material Incentives and Non-Material Incentives on the Work Effectiveness of Employees of the Regional Drinking Water Company (PDAM) of Parepare City. The data collection techniques used in this study were observation and questionnaires. The sample in this study was 112 respondents. The data analysis technique in this study used multiple linear regression analysis. Based on the results of the research that has been done, it shows that: 1) Material incentives have a significant positive effect on the work effectiveness of the employees of the PDAM Parepare. 2) Non-Material Incentives have a significant positive effect on the work effectiveness of the employees of the PDAM Parepare.